2022
DOI: 10.1111/hex.13574
|View full text |Cite
|
Sign up to set email alerts
|

Nursing staff facilitate patient participation by championing the patient's perspective: An action research study in spinal cord injury rehabilitation

Abstract: Introduction Persons with spinal cord injury have experienced a life‐changing event, and they need to engage in the rehabilitation process to adjust to their current situation and future living conditions. Due to the highly contextual and varying psychological and physical ability to participate from patient to patient during rehabilitation, this is difficult for the injured person and for health professionals to support. Therefore, the aim of the study was to develop and facilitate patient participation by en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 62 publications
1
4
0
Order By: Relevance
“…In the exosystem, our results corroborate earlier work which states that it is fundamental that the health care professionals should show respect for the persons' way of doing things and that they are able to demonstrate empathy, sensitivity attentiveness and responsiveness to the individual needs [45,[61][62][63]. Health care professionals with supportive attitudes have been identified by people with SCI as being central to their recovery, well-being, autonomy and hope [64].…”
Section: Positive Attitudes Towards Oneself and From Others In Suppor...supporting
confidence: 87%
“…In the exosystem, our results corroborate earlier work which states that it is fundamental that the health care professionals should show respect for the persons' way of doing things and that they are able to demonstrate empathy, sensitivity attentiveness and responsiveness to the individual needs [45,[61][62][63]. Health care professionals with supportive attitudes have been identified by people with SCI as being central to their recovery, well-being, autonomy and hope [64].…”
Section: Positive Attitudes Towards Oneself and From Others In Suppor...supporting
confidence: 87%
“…This article explores challenges in changes resulting from an action research (AR) study investigating nurses' possibilities to facilitate patient participation in a Danish rehabilitation unit for patients with spinal cord injury ( 1 , 2 ). Despite the co-researchers' new insights, approaches, and actions supporting patient participation, it was not possible to change the basic conditions for nursing practice.…”
Section: Introductionmentioning
confidence: 99%
“…During the AR study by Steensgaard ( 1 ), the involved nurse co-researchers were surprised how little they knew about the patient's situation, perspective, and preferences and how little this knowledge had been included in their nursing so far ( 1 , 2 ). The AR study showed that the patient's perspective was of major importance to the nurses to adjust their care to the patient's needs.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations